Unified approach to fused and spirocyclic oxindoles through lewis-acid-promoted opening of spiroepoxyoxindoles with allylsilanes: application to the formal synthesis of (+/-)-physovenine - Sharma, Brijesh M.; Yadav, Mahesh; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2017)
A protocol for the construction of oxindoles containing all-carbon quaternary centres in a highly regioselective manner has been developed. The reaction involves opening of spiroepoxyoxindoles with allylsilanes to give Hosomi-Sakurai-type products as well as new silicon-containing spirocyclic oxindoles. A formal synthesis of (+/-)-physovenine was accomplished in five steps using this protocol.
Keywords: alkaloids; Allylation; annulation; Lewis acids; spiro compounds